2021
DOI: 10.1007/s13205-021-02892-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical applications of metal oxide nanoparticles in aging and age-associated diseases

Abstract: Metal oxide nanoparticles are known to exhibit unique properties such as catalyzing the neutralization of superoxide anions, hydroxyl radicals, hydrogen peroxides and behave as antioxidant enzymes. Oxidative stress, damage and chronic inflammation are major causes and consequences of aging and age-associated disorders. With the increasing popularity of metal oxide nanoparticles, they have been applied in various age-related pathologies using their antioxidant property. Metal oxide nanoparticles have been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Recent studies have revealed that materials and their oxides can exhibit antioxidant properties when used in the form of nanomaterials. Specific metal oxide nanoparticles, like CeO 2 , selenium (Se), and Cu 5.4 O, demonstrate capabilities akin to antioxidant enzymes such as superoxide dismutase (SOD), catalase, and glutathione peroxidase [156][157][158]. Selenium nanoparticles (SeNPs) are acknowledged for their robust anticancer, antibacterial, antimicrobial, antiviral, anti-inflammatory, and antioxidant characteristics, all of which notably influence the process of wound healing.…”
Section: Novel Metallic Nanomaterialsmentioning
confidence: 99%
“…Recent studies have revealed that materials and their oxides can exhibit antioxidant properties when used in the form of nanomaterials. Specific metal oxide nanoparticles, like CeO 2 , selenium (Se), and Cu 5.4 O, demonstrate capabilities akin to antioxidant enzymes such as superoxide dismutase (SOD), catalase, and glutathione peroxidase [156][157][158]. Selenium nanoparticles (SeNPs) are acknowledged for their robust anticancer, antibacterial, antimicrobial, antiviral, anti-inflammatory, and antioxidant characteristics, all of which notably influence the process of wound healing.…”
Section: Novel Metallic Nanomaterialsmentioning
confidence: 99%
“…Selected metal oxide nanoparticles, such as CeO 2 , behave as antioxidant enzymes, that is, nanozymes in pathological conditions, such as superoxide dismutase, catalase and glutathione peroxidase. Nanozymes have substantial catalytically active surface atoms and thus are highly active, whereas natural enzymes usually have only one active centre, thus making them more efficient in catalytic reactions than natural enzymes 85–88 …”
Section: Scavenging Excessive Rosmentioning
confidence: 99%